Bacterial profiles and volatile flavor compounds in commercial Suancai with varying salt concentration from Northeastern China. (November 2020) - Liang, Huipeng; He, Zhen; Wang, Xinyi; Song, Ge; Chen, Huiying; Lin, Xinping; Ji, Chaofan; Zhang, Sufang
Graphical abstract: Highlights: Firmicutes and Cyanobacteria were major phylum in Suancai. Lactobacillus and Pediococcus were the biomarker of LS and HS, respectively. Lactobacillus and Pediococcus were correlated with flavors in Suancai. The inoculated of P. pentosaceus improve the alcohols and nitriles in Suancai. The co-inoculated of L. plantarum and P. pentosaceus improve the flavors in Suancai. Abstract: Suancai, a popular traditional fermented cabbage in northeast China, is commonly prepared by the spontaneous fermentation process at a certain salt concentration. The salt can affect the metabolites by affecting the microorganisms during Suancai fermentation. The bacterial community and volatile flavor compounds in commercial Suancai from different regions of Northeastern China at different salt concentrations were investigated using next-generation sequencing and GC–MS. Firmicutes and Cyanobacteria were the dominant phyla in the commercial Suancai, and Lactobacillus, Pediococcus, and Leuconostoc were the dominant genera. Among them, Lactobacillus and Pediococcus were considered as the biomarkers of the low and high salt Suncai, respectively. Eighty-five volatile flavor compounds were detected, and HS exhibited higher contents of volatile flavor compounds than LS. Based on the results of correlation analysis, Pediococcus were highly correlated with the alcohols and nitriles in Suancai. The contents of alcohols and nitriles significantly increased in the Suancai, fermented by Pediococcus pentosaceus . The co-inoculated fermentation of Lactobacillus plantarum and P. pentosaceus could increase the concentrations of alcohols, esters, aldehydes, hydrocarbons, and nitriles in Suancai. This study provides a perspective for understanding the ecology of Suancai fermentation and facilitating the fermentation with multispecies inoculation fermentation at an appropriate salt concentration.